Analisa perbedaan kinerja keuangan pada perusahaan Farmasi yang Terdaftar di BEI sebelum dan setelah pengumuman covid-19. - Yuslinda Nasution (Jurnal Manajemen, 2021)
The purpose of this study is to find out if there are differences in financial performance in the time before covid and after covid 19. The population of this study is Pharmaceutical Companies listed on IDX in the period 2019-2020 before covid and after covid. With a sample of 10 companies in this study.The methods used is Paired t-test Sample. The results of this study are no differences in the variable Current Ratio (CR), Earning Per Share (EPS), Book Value (BV), Debt To Asset Ratio (DAR), Debt To Equity Ratio (DER), Return On Asset (ROA), Return On Equity (ROE), and Net Profit Margin (NPM). For the share price there is a significant difference